Квантовий алгоритм шора для вирішення проблеми факторизації числа - Островський, А. М. (ХНУРЕ, 2019)
The given work is devoted to the modern developments in the field of quantum computer algorithms related to cryptanalysis. The major topic of the work is a research of the Shor quantum algorithm that is designed to solve a factorization problem. The work also contains information about the current state of quantum computing technologies and known non-quantum solutions to the factorization problem. The aim of the work is to demonstrate that nowadays-cryptographic systems based on impossibility to find factors of the big number are vulnerable to quantum algorithms or will be vulnerable in the near future.